Does your diagnostic and clinical expertise conflict with your leadership?. Issue 12 (December 2019) - Lees, Peter
Abstract: Research evidence demonstrates that more and better medical leadership leads to higher quality patient care and improved clinical outcomes. Well-rehearsed challenges facing the leadership of healthcare systems across the world call for the ability to lead through growing complexity. Evidence suggests this requires different competencies to the well-honed skills which make clinicians so valued in managing clinically complicated problems. Those 'new' skills can be learned but that requires a shift in culture within the profession and the system as a whole, starting with recognition of the importance of leadership and recognition of the need to support and develop medical leaders. That will require significant investment and ingenuity to incorporate development into already over-full curricula. As most leadership learning is experiential, the bulk of learning must be at the coal-face, not in the classroom and training the trainers would seem to be an inescapable, urgent early step.